Incremental visual servo control of robotic manipulator for autonomous capture of non-cooperative target. (16th November 2016) - Dong, Gangqi; Zhu, Zheng H.
Abstract: This paper develops a new autonomous incremental visual servo control law for the robotic manipulator to capture a non-cooperative target, where the control input is the incremental joint angle to avoid the multiple solutions in the existing inverse kinematics. The position and motion of the non-cooperative target are estimated by an eye-to-hand vision system in real time by integrated photogrammetry and extended Kalman filter. The estimated position and motion of the target are fed into the newly developed position-based visual servo control law to drive the manipulator incrementally towards the dynamically predicted interception point between trajectories of the end effector and the target. To validate the proposed approach, a hardware-in-the-loop simulation has been conducted where the position and motion of the target is estimated by a real eye-to-hand camera and fed into the simulation of the robotic manipulator. The simulation results show the proposed incremental visual servo control law is stable and able to avoid the multiple solutions in the total inverse kinematics. Abstract :